2008
DOI: 10.1093/ndt/gfn356
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal outcome in subjects with K/DOQI stage 1-3 chronic kidney disease: the importance of urinary albumin excretion

Abstract: Subjects with stage 1 or 2 CKD have an increased risk for adverse cardiovascular and renal outcome and should receive equal attention as subjects with stage 3 CKD. Subdividing stage 3 CKD according to the presence or absence of a UAE >30 mg/24 h improves risk stratification within this stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 27 publications
12
99
1
6
Order By: Relevance
“…In the earlier stage of CKD, evaluation of albuminuria and renal function, as well as therapeutic intervention, may be important to prevent future development and progression of CVD, in addition to the development and progression of CKD. [33][34][35] These results thus revealed that CKD is significantly related to MHT and WCHT on the basis of ABP monitoring in the general population. Further prospective studies are needed to clarify the role of ABP measurements in predicting future occurrence of CKD and associated disorders in the general population.…”
Section: Usefulness Of Ambulatory Blood Pressure Monitoring In Ckdmentioning
confidence: 88%
“…In the earlier stage of CKD, evaluation of albuminuria and renal function, as well as therapeutic intervention, may be important to prevent future development and progression of CVD, in addition to the development and progression of CKD. [33][34][35] These results thus revealed that CKD is significantly related to MHT and WCHT on the basis of ABP monitoring in the general population. Further prospective studies are needed to clarify the role of ABP measurements in predicting future occurrence of CKD and associated disorders in the general population.…”
Section: Usefulness Of Ambulatory Blood Pressure Monitoring In Ckdmentioning
confidence: 88%
“…A post hoc analysis from the Prevention of Renal and Vascular End-Stage Disease study 7 showed that a category of subjects with a decreased eGFR but normoalbuminuria was not at increased risk of CVD, and the impact of reduced GFR was shown by PROSPER (Prospective study of Pravastatin in the Elderly at Risk) to be greater for coronary artery disease (CAD) than for stroke in elderly people. 8 We have recently shown that albuminuria, but not reduced eGFR, is associated with not only incident symptomatic stroke 9 but also prevalent silent cerebral infarction 10 in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies carried out in Holland 26 and in the United States 27 have reported a significant increase in the occurrence of cardiovascular events in patients with CKD stage 3B (or eGFR < 45 mL/min/1.73m 2 ) without proteinuria. On the other hand, in a study with patients after myocardial infarction 28 and in two other populationbased studies, 29,30 the risk of cardiovascular events adjusted for age and sex was not statistically elevated in patients with stage 3 CKD and without proteinuria, although it was clearly increased in those who had proteinuria.…”
Section: Prevention Of Medical Error (Drug Nephrotoxicity)mentioning
confidence: 84%
“…Nowadays, however, it is evident that macroalbuminuria also associates with cardiovascular outcomes, 32,33 and microalbuminuria identifies patients with CKD and predicts those who will progress to RRT in diabetes 34,35 or hipertensives, 36 or in the general population. 19,20,29 In conclusion, estimated GFR from plasma creatinine and measurement of microalbuminuria or macroalbuminuria (proteinuria) are simple, widely available, and high relevant clinical tests. They should be regularly performed in patients at the risk of CKD (diabetics, hypertensives, elderly, relatives on RRT), particularly in the pre-clinical stages of the disease (when eGFR is greater than 60 mL/min/1.73m 2 ), as well as in patients with CVD.…”
Section: Prevention Of Medical Error (Drug Nephrotoxicity)mentioning
confidence: 99%